Characterization of bioactive and antioxidant composition of mountain tea (Sideritis montana ssp. montana): Microwave-assisted technology - Akbaba, Emel (Pamukkale University, 2021)
The use of synthetic antioxidants has been restricted and even prohibited in some countries due to their toxic effects. This study aims to perform the biochemical assays representing the bioactive compounds in Sideritis montana L. ssp. montana L. known as mountain tea. The study specifically investigates the potential application of mountain tea in the food industry as a natural antioxidant. Different extraction procedures using various solvents are carried out to obtain phenolic compounds and antioxidant activities in plant matrices. In this study, the maceration method was used for the extraction procedure. Furthermore, the microwave-assisted extraction method was applied to shorten the extraction time and decrease the solvent quantity. Methanol was used as a solvent in both conventional and microwave-assisted extraction procedures. The samples were evaluated in terms of the total phenolic compounds, total flavonoids, antioxidant activities, and metal chelating capacity. The obtained results for classical extraction and microwave-assisted extraction methods were found to be 51 and 55 mg/g for TPC, 16.3 and 22 mg/g for TFC, 93 and 103 mg/g for FRAP, and 284 and 282 mg/g for MCC, respectively. The microwave-assisted extraction method produced higher concentrations of bioactive molecules as compared to the classical method. Microwave-assisted extraction was found to be superior to the conventional method in terms of effectiveness, extraction time, and solvent quantity. Besides, Sideritis montana ssp. montana is suggested in the food industry as a natural antioxidant instead of synthetic ones to prevent health-damaging effects. © 2021 IJSM.
Keywords: Antioxidant; Microwave-assisted extraction; Mountain tea; Phenolics; Sideritis